Original paperAllergy to lidocaine injections: comparison of patient history with skin testing in five patients - Jenerowicz, Dorota; Polańska, Adriana; Glińska, Olga; Czarnecka-Operacz, Magdalena; Schwartz, Robert A. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: True allergy to local anesthetics, especially lidocaine, is uncommon. Most adverse reactions to this group of medications are classified as psychomotor, autonomic or toxic. In the case of suspected hypersensitivity to local anesthetics, skin testing is considered to be a useful tool – patch tests and intradermal tests for delayed hypersensitivity and skin prick tests and intradermal tests for immediate reactions. There is a particular need for such a diagnostic procedure, as patients suspected of hypersensitivity to local anesthetic drugs are frequently admitted. Aim: To highlight the problem of hypersensitivity to local anesthetics on the basis of authors' own experience and literature data. Material and methods : We present cases of 5 patients referred to the clinic by their dentists with a suspicion of allergy to local anesthetics, four to lidocaine and 1 to articaine. Results: Intradermal tests were positive in 1 out of 5 subjects, with a concomitant episode of urticaria. In 1 patient we obtained a doubtful result of intradermal tests. Skin prick tests and patch tests were negative in all cases. In 2 cases we performed an incremental challenge test also with a negative result. Conclusions : It has to be emphasized that, although rare, consequences of true allergy to local anesthetics can be serious considering a patient’s future management and therapy. That is why this diagnosis may be crucial.